Open government data initiatives in Europe: northern versus southern countries analysis - Gomes, Álvaro (2014)
This paper explores a set of national European open government data. The study is particularly focused on analyzing and identifying differences on how northern and southern countries of Europe have adopted, accepted and promoted open government data portals. Using web content analysis, open government data portals of six countries, three from the Northern Europe region (Denmark, Norway, and United Kingdom) and three from the Southern European region (Italy, Portugal, and Spain) are scrutinized for understanding the status of open government data initiatives. The results of the direct content analysis observation point to the existence of some currently differences among the countries of the two regions, mainly in what concerns their ability to reuse open data made available by public entities. Some possible reasons for that are advanced and further streams of research to deep the understanding of those reasons are proposed. This way this paper offers new understanding of the current open government data efforts development.